Chemically Programmable and Switchable CAR‐T Therapy. Issue 29 (18th May 2020) - Qi, Junpeng; Tsuji, Kohei; Hymel, David; Burke, Terrence R.; Hudecek, Michael; Rader, Christoph; Peng, Haiyong
Abstract: Although macromolecules on cell surfaces are predominantly targeted and drugged with antibodies, they harbor pockets that are only accessible to small molecules and constitutes a rich subset of binding sites with immense potential diagnostic and therapeutic utility. Compared to antibodies, however, small molecules are disadvantaged by a less confined biodistribution, shorter circulatory half‐life, and inability to communicate with the immune system. Presented herein is a method that endows small molecules with the ability to recruit and activate chimeric antigen receptor T cells (CAR‐Ts). It is based on a CAR‐T platform that uses a chemically programmed antibody fragment (cp‐Fab) as on/off switch. In proof‐of‐concept studies, this cp‐Fab/CAR‐T system targeting folate binding proteins on the cell surface mediated potent and specific eradication of folate‐receptor‐expressing cancer cells in vitro and in vivo. Abstract : Fab‐ulous ! A novel small‐molecule‐controlled chimeric antigen receptor T cell (CAR‐T) therapy was developed based on a chemically programmed antibody fragment (Fab) as an on/off switch. As a proof‐of‐concept, a folate‐programmed Fab switch mediated potent and specific eradication of folate‐receptor‐expressing cancer cells by engaging CAR‐T cells in both in vitro and in vivo models of ovarian cancer.